Mouse models of thyroid cancer: A 2015 update. (5th February 2016) - Kirschner, Lawrence S.; Qamri, Zahida; Kari, Suresh; Ashtekar, Amruta
Abstract: Thyroid cancer is the most common endocrine neoplasm, and its rate is rising at an alarming pace. Thus, there is a compelling need to develop in vivo models which will not only enable the confirmation of the oncogenic potential of driver genes, but also point the way towards the development of new therapeutics. Over the past 20 years, techniques for the generation of mouse models of human diseases have progressed substantially, accompanied by parallel advances in the genetics and genomics of human tumors. This convergence has enabled the development of mouse lines carrying mutations in the genes that cause thyroid cancers of all subtypes, including differentiated papillary and follicular thyroid cancers, poorly differentiated/anaplastic cancers, and medullary thyroid cancers. In this review, we will discuss the state of the art of mouse modeling of thyroid cancer, with the eventual goal of providing insight into tumor biology and treatment. Highlights: Mutations which cause thyroid cancer in humans have been modeled in mice. Multiple hits are required for metastatic follicular thyroid or anaplastic cancer. Medullary thyroid cancer is modeled by mutations in Rb or cell cycle control genes. Genetic mouse models are good pre-clinical tools for the development of new therapies.